Toughening of epoxy resins by amine terminated poly(arylene ether ketone)s having pendant tertiary butyl groups - (:unkn) unknown (SPRINGER, 2007)
The objective of this study was to investigate the effects of the amine terminated poly(arylene ether ketone) (PAEK) oligomers as epoxy tougheners on the mechanical and thermal properties of diglycidyl ether of bisphenol A based epoxy resin. The reactive oligomers including pendant tertiary butyl groups were synthesized by nucleophilic aromatic substitution reaction and molecular weight of the oligomers were controlled through end group functionalization and characterized by FTIR spectroscopy. The stoichiometrical amount of the reactive oligomers as toughener and the curing agent, 4,4'-diaminodiphenyl sulfone (DDS) were mixed and degassed. The homogenous mixtures were cured at 120 degrees C into the preheated molds. The mechanical and thermal characterizations of toughened epoxy resin system were evaluated. It has been shown that the mechanical and thermal properties of toughened epoxy system vary as a function of the chemical structure and the concentration of reactive oligomers.
Keywords: amine terminated oligomers; toughening; epoxy curing; poly(arylene ether ketones); STOICHIOMETRY; RUBBER